2019
DOI: 10.1093/femsyr/foz078
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the peroxin Pex34p suppresses impaired acetate utilization in yeast lacking the mitochondrial aspartate/glutamate carrier Agc1p

Abstract: PEX34, encoding a peroxisomal protein implicated in regulating peroxisome numbers, was identified as a high copy suppressor, capable of bypassing impaired acetate utilization of agc1∆ yeast. However, improved growth of agc1∆ yeast on acetate is not mediated through peroxisome proliferation. Instead, stress to the endoplasmic reticulum and mitochondria from PEX34 overexpression appears to contribute to enhanced acetate utilization of agc1∆ yeast. The citrate/2-oxoglutarate carrier Yhm2p is required for PEX34 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Enhanced chronological lifespan can also be mediated by the activation of mitochondrial retrograde and oxidative stress responses to overcome mitochondrial stresses [38,39]. We have previously shown that PEX34 over-expression induced mitochondrial retrograde signaling in acetate medium [37], suggesting that PEX34 over-expression can induce these stress responses resulting in increased longevity in yeasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced chronological lifespan can also be mediated by the activation of mitochondrial retrograde and oxidative stress responses to overcome mitochondrial stresses [38,39]. We have previously shown that PEX34 over-expression induced mitochondrial retrograde signaling in acetate medium [37], suggesting that PEX34 over-expression can induce these stress responses resulting in increased longevity in yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…Gpd1p is required for glycerol production, which can protect cells under several stress conditions, such as osmotic stress, oxidative stress, or ER stress [35,36]. Our group has previously shown that PEX34 over-expression results in aberrant ER morphology and induces ER stress in an acetate medium [37]. It is possible that PEX34 over-expression also induces ER stress in the stationary phase of glucose-grown cells, resulting in the induction of GPD1-mediated NAD + regeneration in peroxisomes.…”
Section: Discussionmentioning
confidence: 99%
“…Another illustration is the mammalian MCS between lysosomes, POs, and the ER, involved in cholesterol transport between the lysosomes and the ER, via the POs ( Chu et al, 2021 ; Xiao et al, 2019 ). Citrate is transferred from POs to mitochondria through expanded contact sites following PEX34 overexpression in yeast ( Chalermwat et al, 2019 ). Very long chain fatty acids (VLCFA) are transported by the MCS involving VAPB and ACBD4/5 ( Costello et al, 2017 ).…”
Section: Regulation Of Peroxisomal And/or Mitochondrial Divisionmentioning
confidence: 99%
“…Yeast transformations were performed using the lithium acetate procedure [81] and transformants were selected using synthetic complete (SC) medium lacking uracil. Promoter-lacZ reporter plasmids pLJ519 (ACT1-lacZ) and pLJ440 (FET3-lacZ) have been previously described [82,83].…”
Section: Yeast Strains Culture Conditions and Plasmidsmentioning
confidence: 99%